Polypropylene-based Composites Reinforced with Waste Tropic Wood Flours: Determination of Accelerated Weathering Resistance, Tribological, and Thermal Properties - Basboga, Ibrahim Halil (North Carolina State Univ Dept Wood & Paper Sci, 2023)
This study investigated the effects of Iroko wood flour (WF) and nano -titanium dioxide (TiO2) concentration on the properties of polypropylene (PP)-based composites, including accelerated weathering resistance, tribological behavior, thermal stability, physical characteristics, mechanical strength, morphological features, color changes, and surface roughness. The results showed that the presence of WF and TiO2 significantly influenced the density, hardness, thermal stability, crystallinity, coefficient of friction, and wear rate of the composites. Both fillers positively impacted the tensile strength, flexural strength, and flexural modulus of the composites, although the elongation at break values decreased. TiO2 addition enhanced thermal stability and protection against UV radiation, whereas using wood flour negatively affected color properties. Moreover, the surface roughness of the composites was affected by weathering time and wood flour content. These findings highlight the potential of WF and TiO2 as effective fillers for enhancing PP-based composites' properties and weathering resistance.
Keywords: Wood plastic composite; Iroko wood flour; UV aging; Tribological properties